Differences in the Attitudes of Fourth Grade Pupils of the Elementary School According to the Teaching of Physical Education in Terms of Gender - Katarina Dragutinovic; Milena Mitrovic (Journal of Anthropology of Sport and Physical Education)
The main aim of this research was to determine the diff erences in attitudes between boys and girls of the fourth grade towards the continuation of physical education. The sample of respondents was 121 pupil of the elementary school “Vuk Karadžić“ from Podgorica. Students are divided into 2 sub-samples according to the gender criterium (74 boys, 47 girls). We used an anonymous standardized questionnaire adapted to this research. The results were processed descriptively and tabulated. A H2 test was used to determine statistically signifi cant diff erences. The results showed that diff erences between boys and girls appear only in favorite sports, while in other issues there are no statistically signifi cant diff erences.